The Influence of Product Innovation and Price Promotion on Consumer Purchase Interest in Banana Rolls MSMEs in Cirebon City - ADIANSYAH, Aji; SAHARA, Sahara; KUSTANDI, Tedi (International Journal of Environmental, Sustainability, and Social Science, 2025)
This study aims to analyze the influence of product innovation and price promotions on consumer purchasing interest in Banana Rolls Micro, Small, and Medium Enterprises (MSMEs) in Cirebon City. This study uses a quantitative research type with a survey approach. The quantitative method was chosen because it allows researchers to test predetermined hypotheses through numerical data collection and statistical analysis. Data were collected from 93 Banana Rolls consumer respondents through a questionnaire. Data analysis was conducted using multiple linear regression after undergoing validity, reliability, and classical assumption tests (normality, linearity, multicollinearity, and autocorrelation). The results show that product innovation and price promotions, both partially and simultaneously, have a positive and significant effect on consumer purchasing interest. Product innovation contributes more to increasing purchasing interest than price promotions. These findings underscore the importance of an integrated marketing strategy that prioritizes creative product development and attractive price offers to increase competitiveness and consumer loyalty in the culinary MSME sector.